PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 PADANG - Putri Oviolanda Irianto (Riksa Bahasa, 2016)
The purpose of this study was to describe the effects of cooperative learning "think pair share" the learning outcomes of students of class VII SMPN 1 Padang in writing the descriptive text. The method used in this study is quasi-experimental. Data collected from the pretest and posttest for the implementation of learning. The results showed theaverage value of pretest 69.63, and after learning by using models think pare share, the results showed 89.07, with good qualifications. In conclusion, cooperative learning to think pare share type can improve the ability to write descriptive text for students of SMPN 1 Padang.Keywords: cooperative learning, "think pare share", write the description text.